Pengaruh Kompetensi, Pengalaman, Motivasi, Dan Kecerdasan Emosional Terhadap Efektivitas Kepemimpinan Dan Kinerja Organisasi : Studi Literatur Sistematis - Hendriarto, Prasetyono (OGZ Research & Publishing, 2025)
This study aims to systematically examine the influence of competence, work experience, motivation, and emotional intelligence on leadership effectiveness and organizational performance. Employing a systematic literature review approach, 20 relevant scholarly articles from various sectors—including education, government, and private organizations—were analyzed. The articles were selected based on stringent inclusion and exclusion criteria and evaluated using thematic content analysis within the PRISMA framework. The results show that all four variables significantly contribute to leadership effectiveness and organizational performance, with emotional intelligence emerging as the most dominant factor (supported by 17 studies), followed by competence (16), motivation (14), and experience (13). These findings highlight that effective leadership is not only driven by technical skills and experience but is also strongly influenced by the leader’s ability to manage emotions and intrinsic motivation. This research contributes to the development of personality- and emotion-based leadership models and provides valuable insights for strategic human resource development in modern organizational contexts. Future studies are encouraged to adopt quantitative approaches and explore underrepresented sectors to enrich the generalizability of findings.